Relationship Between Myopia and Other Risk Factors With Anxiety and Depression Among Chinese University Freshmen During the COVID-19 Pandemic - Zhang, Hongmei; Gao, Huijuan; Zhu, Yun; Zhu, Ying; Dang, Weiyu; Wei, Ruihua; Yan, Hua (Frontiers in Public Health, 2021)
Purpose: To investigate the association of myopia and other risk factors with anxiety and depression among Chinese university freshmen during the coronavirus disease 2019 (COVID-19) pandemic. Methods: This cross-sectional study was conducted at Tianjin Medical University from October 2020 to December 2020. Ophthalmic examination of the eyes was performed by an experienced ophthalmologist. Detailed information on depression, anxiety, and other risk factors was collected via the Self-rating Anxiety Scale (SAS) and Self-rating Depression Scale (SDS). Results: The overall prevalence of anxiety and depression in our study was 10.34% and 25.13%, respectively. The prevalence of myopia and high myopia was 92.02% and 26.7%, respectively. There were significant associations between anxiety and spectacle power [odds ratios (OR)=0.89; 95% confidence intervals (CI): 0.81-0.98, P=0.019], sphere equivalent (OR=0.89; 95% CI: 0.81- 0.98, P=0.025), sleep time (OR=0.53; 95% CI: 0.35-0.79, P=0.002), and body mass index (OR=0.93; 95% CI: 0.86-0.99, P=0.047). In the multivariable linear regression models, spectacle power (B = -0.43; 95% CI: -0.68 to -0.19, P=0.001) and sphere equivalent (B = -0.36; 95% CI: -0.60 to -0.11, P=0.005) were negatively associated with anxiety scores, whereas axial length (B=0.54; 95% CI: 0.02-1.07, P=0.044) was positively correlated with anxiety scores. Every 1-h decrease in sleep time was associated with a 0.12-point increase in depression score. Conclusion: Myopia was associated with anxiety and anxiety scores. The greater the degree of myopia, the higher the anxiety score. However, myopia was not found to be associated with depression. The results highlight the importance of providing psychological support to students with myopia during the COVID-19 pandemic.